Search for a heavy toplike quark in pp collisions at √s=1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We present the results of a search for pair production of a heavy toplike (t') quark decaying to Wq final states using data corresponding to an integrated luminosity of 5.6 fb(-1) collected by the CDF II detector in pp collisions at √s=1.96 TeV. We perform parallel searches for t'→Wb and t'→Wq (where q is a generic down-type quark) in events containing a lepton and four or more jets. By performing a fit to the two-dimensional distribution of total transverse energy versus reconstructed t' quark mass, we set upper limits on the t't' production cross section and exclude a standard model fourth-generation t' quark decaying to Wb (Wq) with mass below 358 (340) GeV/c(2) at 95% C.L.